Context-Aware Adaptation of Component-Based Systems: An Active Repository Approach - Sindolfo Miranda Filho; Julio Melo; Luiz Eduardo Leite; Guido Lemos (Journal of Computer Networks and Communications)
Context-aware systems are able to monitor and automatically adapt their operation accordingly to the execution context in which they are introduced. Component-based software engineering (CBSE) focuses on the development and reuse of self-contained software assets in order to achieve better productivity and quality. In order to store and retrieve components, CBSE employs component repository systems to provide components to the system developers. This paper presents an active component repository that is able to receive the current configuration from the context-aware system and compute the components and the new architecture that better fit the given context. Since the repository has a wide knowledge of available components, it can better decide which configuration is more suitable to the running system. The repository applies Fuzzy logic algorithm to evaluate the adequacy level of the components and GRASP algorithm to mount the new system architecture. In order to verify the feasibility of our approach, we use a digital TV middleware case study to achieve experimental results.